2015
DOI: 10.1155/2015/283796
|View full text |Cite
|
Sign up to set email alerts
|

PreliminaryIn VitroAssessment of Stem Cell Compatibility with Cross-Linked Poly(ε-caprolactone urethane) Scaffolds Designed through High Internal Phase Emulsions

Abstract: By using a high internal phase emulsion process, elastomeric poly(ε-caprolactone urethane) (PCLU) scaffolds were designed with pores size ranging from below 150 μm to 1800 μm and a porosity of 86% making them suitable for bone tissue engineering applications. Moreover, the pores appeared to be excellently interconnected, promoting cellularization and future bone ingrowth. This study evaluated the in vitro cytotoxicity of the PCLU scaffolds towards human mesenchymal stem cells (hMSCs) through the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
0
34
0
2
Order By: Relevance
“…The earliest reported PolyHIPE made from PCL was created by copolymerisation of PCL diacrylate with non-degradable monomers (Busby et al, 2001). Various diluting solvents were included in HIPE composition to reduce the viscosity of PCL (Busby et al, 2001;David and Silverstein, 2009;Changotade et al, 2015). Johnson et al reported the incorporation of 76% PCL triacrylate into HIPE composition when DCE used as a porogenic solvent (Johnson et al, 2015).…”
Section: Degradable Polymersmentioning
confidence: 99%
“…The earliest reported PolyHIPE made from PCL was created by copolymerisation of PCL diacrylate with non-degradable monomers (Busby et al, 2001). Various diluting solvents were included in HIPE composition to reduce the viscosity of PCL (Busby et al, 2001;David and Silverstein, 2009;Changotade et al, 2015). Johnson et al reported the incorporation of 76% PCL triacrylate into HIPE composition when DCE used as a porogenic solvent (Johnson et al, 2015).…”
Section: Degradable Polymersmentioning
confidence: 99%
“…Biomaterial cytotoxicity can emanate from the original material itself and from the by-products that may leach out from the material 45 . The cytotoxicity of the seven scaffolds' (H1 and H5) extracts was estimated by evaluating the viability of HuGu cells using an MTT assay.…”
Section: Figure 4 34 Cytotoxicity Of the Prepared Scaffoldsmentioning
confidence: 99%
“…Indeed, elastomeric scaffolds can be used to regenerate soft and dynamic tissues such as skin, tendons, and muscles, since the mismatch of Young moduli is reduced and the material is able to recover large mechanical deformations. CSPBAT has developed biodegradable poly(ester-urethane)-based scaffolds (PCLU) that can support the adhesion of cells [12]. This study shows the potential of the combination use of the nanoindentation tests, the pulse-echo ultrasonic technique and of the µ-Brillouin spectroscopy vs temperature to assess some dynamical viscoelastic parameters of elastomeric scaffolds at very different frequencies (Hz-100 THz).…”
Section: Introductionmentioning
confidence: 89%
“…PCLU scaffolds were obtained through a high internal phase emulsion process named polyHIPE, and characterized by determination of their density, porosity and pore inter-connectivity, as previously described [12]. The glass transition temperature was estimated below -80°C by differential scanning calorimetry.…”
Section: Elaboration and Characterization Of Pclu Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation